2016
DOI: 10.1016/j.jalz.2016.06.1567
|View full text |Cite
|
Sign up to set email alerts
|

P2‐356: Sense of Location in People with Alzheimer's Disease

Abstract: Results: The data show that levels of total and individual phospholipids (except for phosphatidylinositol), as well as those of the preand post-synaptic proteins Synapsin-1 and PSD-95, were significantly enhanced by combined supplementation of FO plus uridine and AOX and not enhanced by supplementation of FO plus uridine without AOX. Brain and plasma DHA, EPA and total omega-3 fatty acids increased while arachidonic acid (AA) and total omega-6 fatty acids were decreased in rats receiving the FO plus uridine. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Regarding linear deviation as a reference for diagnostic power, a deviation of 16 m was set as cutoff for comparison (Pai et al, 2016 ). The hit rates were 0.86, 0.54, and 0.05 for CU, prAD, and AD, respectively ( p < 0.001, post hoc comparisons AD vs. prAD, p < 0.001; AD vs. CU, p < 0.001; prAD vs. CU, p < 0.01; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding linear deviation as a reference for diagnostic power, a deviation of 16 m was set as cutoff for comparison (Pai et al, 2016 ). The hit rates were 0.86, 0.54, and 0.05 for CU, prAD, and AD, respectively ( p < 0.001, post hoc comparisons AD vs. prAD, p < 0.001; AD vs. CU, p < 0.001; prAD vs. CU, p < 0.01; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The length of the path was 660 m, on which five sites (A–E) were carefully chosen to prevent individuals from seeing the starting point. The participants, prior to the experiment, were instructed to approach the five target sites one after another and touch the screen of a tablet personal computer (PC) with an innovatively designed Pai-Jan (PJ) device (Pai et al, 2016 ) upon judging that they had reached the target. Figure 1A provides an aerial photo of the campus and the PJ device interface on which the designed path and the location of the target sites were shown.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that individuals with SCD, MCI, and dementia report spatial navigation complaints on SSNCQ-s more frequently than CN older adults [33]. Other studies have shown that QuENA can identify individuals with AD dementia who experience episodes of getting lost [34] and that QuENA-i in particular can predict the occurrence of these episodes over a three-year period [35]. The present study was the rst to comprehensively evaluate the potential of several self-and informant-reported spatial navigation questionnaires (i.e., SSNCQ, SBSOD, and QuENA) to discriminate between CN older adults and participants from the memory clinic cohort, including individuals with SCD, aMCI, and mild dementia de ned by clinical criteria and strati ed by biomarkers.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by the results of previous studies showing that self-reported spatial navigation de cits are related to AD pathology in cognitively normal older adults as measured by levels of amyloid-β in CSF [27,32] and are common in memory clinic cohorts, including individuals with SCD, aMCI and AD dementia [33]. Both self-and informant-reported spatial navigation questionnaires have been shown to identify individuals with AD dementia with episodes of getting lost [34], but only informant-reported questionnaires predicted getting lost episodes over a three-year period [35]. It is worth noting that self-reported spatial navigation abilities may be in uenced by anxiety and depressive symptoms [33,36].…”
Section: Introductionmentioning
confidence: 99%